2014
DOI: 10.1016/j.beproc.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees sometimes see fuller as better: Judgments of food quantities based on container size and fullness

Abstract: The context in which food is presented can alter quantity judgments leading to sub-optimal choice behavior. Humans often over-estimate food quantity on the basis of how food is presented. Food appears larger if plated on smaller dishes than larger dishes and liquid volumes appear larger in taller cups than shorter cups. Moreover, smaller but fuller containers are preferred in comparison to larger, but less full containers with a truly larger quantity. Here, we assessed whether similar phenomena occur in chimpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…This effect diminished for some chimpanzees when we introduced a larger discrepancy (2-item difference) between sets in Phase 2. These were clear errors with regard to maximizing intake, and were consistent with previous studies that have reported failures by chimpanzees to select the larger quantity as a function of presentation style or set composition (e.g., Beran et al, 2008; Boysen et al, 2001; Parrish and Beran, 2014b). …”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…This effect diminished for some chimpanzees when we introduced a larger discrepancy (2-item difference) between sets in Phase 2. These were clear errors with regard to maximizing intake, and were consistent with previous studies that have reported failures by chimpanzees to select the larger quantity as a function of presentation style or set composition (e.g., Beran et al, 2008; Boysen et al, 2001; Parrish and Beran, 2014b). …”
Section: Methodssupporting
confidence: 90%
“…Chimpanzees participated for preferred food rewards and were otherwise maintained on their normal diet of fruit, vegetables, and primate chow (no food or water deprivation was used). All four chimpanzees had extensive prior experience making choices between different quantities of foods (e.g., Beran 2001, 2004, 2012; Beran and Beran 2004; Beran et al, 2009a, b; Parrish and Beran, 2014a, b; Rumbaugh et al, 1987). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimpanzees fall prey to the same bias. When given marshmallows or gelatin in small or large transparent cups, they preferred cups that looked more filled, even if those contained a smaller amount of food (Parrish & Beran, 2014a; Figure 3). Even aspects of food items that do not impact their quality or quantity, such as their wholeness, seem to affect chimpanzee choice behavior.…”
Section: Biases and Context Effectsmentioning
confidence: 99%
“…When humans look at food, their perception of portion sizes can be strongly affected by the context in which that food is presented. The size, the color, and the shape of containers holding food directly impact how people estimate the amount of food they are looking at (e.g., Wansink, Parrish and Beran (2014a). These arrangements were used to mimic the Delboeuf illusion in a food discrimination task.…”
Section: Biases and Context Effectsmentioning
confidence: 99%